Retrospective seven years analysis of dexamethasone therapy term pregnancy admitted to hospital university sains malaysia from the year 2003 to 2009 - Ridzuan, Roslan (2010)
Introduction Prematurity is the main cause of neonatal morbidity and mortality. Antenatal corticosteroid therapy has been shown to markedly reduced complications of prematurity. A complete course of antenatal corticosteroid treatment is recommended to prevent pulmonary complications of preterm infants. Repeating courses of antenatal corticosteroid in mothers who are at risk of preterm delivery is still debatable. Objectives The primary objective of the study is to examine the association between different doses of antenatal intramuscular (IM) dexamethasone therapy and fetal respiratory outcomes. Methodology Retrospective study on case records of patients who delivered preterm and received antenatal IM dexamethasone therapy in HUSM from the year 2003 to 2009. Those who received IM dexamethasone 12.5 mg upon admission or diagnosis, followed by another dose of IM dexamethasone 12.5 mg, 12 hours later (total of 25 mg per day), is defined to receive a complete course of IM dexamethasone. Those who did not complete two doses of IM dexamethasone 12.5 mg, 12 hours apart is defined to receive incomplete course of IM dexamethasone. Those who were given another doses of IM dexamethasone after 1 week or more of the first course, is defined to receive repeat course of IM dexamethasone. Their babies’ case records were reviewed to assess the fetal respiratory outcomes. Results We reviewed 927 case records of mothers who delivered preterm in HUSM from the year 2003 to 2009, and 980 case records of their newborns. There were 407 of mothers received incomplete, 484 received complete and 36 received repeat course of IM dexamethasone. Thence, 435 infants exposed to incomplete, 503 infants exposed to complete and 42 infants exposed to repeated courses of antenatal IM dexamethasone for analysis. There were 61 infants delivered at 24 to 28 completed weeks, 515 infants delivered at more than 28 to 34 completed weeks, and 404 infants delivered at more than 34 to less than 37 completed weeks. In the group of infants who were delivered at more than 28 to 34 completed weeks gestation, a complete course of antenatal IM dexamethasone is significantly associated with better respiratory outcomes compared to those infants who were exposed to an incomplete course of antenatal IM dexamethasone. However, in the group of infants who were delivered at 24 to 28 completed weeks gestation as well as those delivered at more than 34 to less than 37 completed weeks period of gestation, there was no significant association between complete or incomplete course of antenatal IM dexamethasone and the respiratory outcomes. Conclusions A complete course of antenatal IM dexamethasone therapy significantly reduces the respiratory complications in the preterm infants delivered at more than 28 to 34 completed weeks period of gestation compared to those who were exposed to incomplete course of antenatal IM dexamethasone.